A 0.5V 110nW Sensor for Temperature Monitoring of Perishable Foods - R. Dastanian; M. Askari (Radioengineering, 2021)
Real-time monitoring solution is essential for the perishable food to estimate the food quality and to predict its shelf life. In this paper an on-chip temperature sensor which is applicable for UHF RFID passive tag is proposed. MOSFET is used as the sensitive element to the temperature. Since the transistors are biased in sub-threshold region, the power consumption is decreased. To converting proportional-to-absolute-temperature (PTAT) and complimentary-to-absolute-temperature (CTAT) voltages to the digital code, the delay generator and 8-bit ripple counter are utilized. For designing binary counter, a low power and high speed D-flip flap (D-FF) based on gate diffusion input (GDI) technique is employed. The proposed temperature sensor dissipates 110nW power while the supply voltage is 0.5 V. Simulated in TSMC 0.18 µm CMOS technology, the total chip area is 0.0104 mm^2 and the error is -0.3/0.7°C in the temperature range of -20°C to 10°C.